1961
DOI: 10.1115/1.3658953
|View full text |Cite
|
Sign up to set email alerts
|

Flow Models in Boundary-Layer Stall Inception

Abstract: Physical evidence on stall inception from visual studies, mean-velocity-profile correlations, shear measurements, and fluctuations in separating boundary layers in the neighborhood of stall are discussed. Direct visual studies suggest that stall inception in the laminar boundary layer follows the classical model, but does not necessarily do so in the turbulent shear layer. It is useful to describe stall as a certain type of transition region, which can be long or short. Adoption of these ideas is shown to lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…The line h = 1.5Λ was discussed by Simpson (1989), who stated that the data of Perry & Schofield (1973) supported the hypothesis that this characterized a path for detaching flow. Another line is h = 1/(2 − Λ) proposed by Sanborn & Kline (1961). They suggested that at a given Λ, h greater than this value would indicate appreciable intermittent backflow.…”
Section: H-λ Relationmentioning
confidence: 98%
“…The line h = 1.5Λ was discussed by Simpson (1989), who stated that the data of Perry & Schofield (1973) supported the hypothesis that this characterized a path for detaching flow. Another line is h = 1/(2 − Λ) proposed by Sanborn & Kline (1961). They suggested that at a given Λ, h greater than this value would indicate appreciable intermittent backflow.…”
Section: H-λ Relationmentioning
confidence: 98%
“…͑12͒ into Eq. ͑6͒ and clearing terms yields: (13) where the term involving ϪdP ϱ /dx has been cancelled by the U ϱ dU ϱ /dx term from Euler's equation for the external flow.…”
Section: Review Of the Castilloõgeorge Analysismentioning
confidence: 99%
“…The integral properties corresponding to separation agree well with the separation criteria of Sandborn and Kline. 9 Downstream of the separation the outer region velocity profiles show some similarity and the chordwise development of the mean velocity is found to be reducible to a universal curve.…”
Section: Discussionmentioning
confidence: 95%